Kemampuan BERBAHASA pada Anak Masa Tahap Sensorimotor - Djokowidodo, AG. Djokowidodo (Widya Warta, 2018)
An adult does not master language skills suddenly, but he acquires continuously since he was an infant. Since then, one began to acquire many particular words which are mainly exposed to him by parents or the ones who take care of the infant. If an infant or toddler has a good development, he will understand better what he senses what he looks at, and what he listens. When infant begins to understand something in his mind and motoric system of speech organ develop, he will try to communicate all of them to others in verbal form , it is possibly universal at the end of sensorimotor period. On the other hand, the Indonesian children’s language skills development which includes development of phonologies, morphologies, syntax, and semantic-lexicon, also, basically are universal at the end of sensorimotor period. It is suggested that the infant’s and toddler’s language skills is need to investigated deeply since there are many factors which influenced cognitive competence, language skills, or both of them, such as child’s caretaking pattern, health condition, or social interaction with his environment. Therefore, the result hopefully would enrich the study of Indonesian children development of language acquisition who have various mother tongue background. Hence, it is possibly universal at the end of sensorimotor period, especially syntax, and semantic-lexicon, also, basically are universal at the end of sensorimotor period. But only the process to master the skills differentiate the language skills development.The process including communication, monolingual, natural, and simple word or sentence.